Melatonin reduces myocardial cell damage in myocardial ischemia/reperfusion rats by inhibiting NLRP3 activation: Melatonin reduces myocardial cell damage - Li, Shurong; Li, Xiang; Xie, Fang; Bai, Yang; Ma, Jun (Cellular and Molecular Biology, 2023)
Melatonin (Mel) is an endogenous hormone with many pharmacological effects, such as sedation, hypnosis, antidepressant, blood pressure regulation, anti-inflammatory and anti-tumor. It is mainly synthesized by pineal gland in vivo. Mel can regulate the function of cardiovascular system and effectively reduce myocardial cell injury, thus playing a role in myocardial protection, but its specific mechanism is unclear. Ischemia-reperfusion injury (IRI) often leads to poor prognosis and complications in patients with cardiovascular diseases, and inflammatory reaction mediated by nod-like receptor thermoprotein domain-related protein 3(NLRP3) is an important reason for the further aggravation of subsequent injury after IRI. Rats were intervened with Mel or NLRP3 inhibitor MCC950 for 10 days, and then the IRI rat model was established. After that, rats were anesthetized and killed, and myocardial tissues were collected for experiments. The experimental results showed that Mel reduced the myocardial infarction area, decreased aspartate aminotransferase (AST), creatine kinase myocardial band (CK-MB), lactate dehydrogenase (LDH) and malondialdehyde (MDA), and significantly inhibited the expression of reactive oxygen species (ROS), NLRP3, caspase-1 and apoptosis-associated speck-like protein containing a CARD (ASC), but its effect on superoxide dismutase (SOD) was opposite. Therefore, Mel may improve autophagy and inflammation during myocardial ischemia/reperfusion and may decrease myocardial cell damage by inhibiting NLRP3.